2014
DOI: 10.5455/msm.2014.26.292-296
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prognostic Factors on Overall Survival in Myelodysplastic Syndromes

Abstract: Background:Accurate prediction of a patient's prognosis is useful to define the risk posed by the disease. Age, gender, peripheral blood cytopenia, proportion of bone marrow (BM) blasts, performance status, comorbidities, transfusion dependence, specific karyotype abnormalities and molecular biomarkers can refine the prediction of prognosis in MDS.Aim:to assess the influence of the some prognostic factors like age, gender, cytopenia, BM blast percentage, transfusion dependence, ferritin, hemoglobin (Hb), lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Likewise, type B studies reported improved 2 year OS in TI patients (51.8% vs 22.5%, P < .0001) 18 ; median OS was longer in patients who achieved TI ≥8 weeks (4.3 years; 95% CI: 3.6‐5.9) than in non‐responders (2.0 years; 95% CI: 1.3‐2.2; P < .0001) 22 . Of the type C studies, no significant difference in OS was observed between patients with a high transfusion burden compared to patients who required ≤18 units of RBC over a period of 3 years of follow‐up ( P = .72185) 23 …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Likewise, type B studies reported improved 2 year OS in TI patients (51.8% vs 22.5%, P < .0001) 18 ; median OS was longer in patients who achieved TI ≥8 weeks (4.3 years; 95% CI: 3.6‐5.9) than in non‐responders (2.0 years; 95% CI: 1.3‐2.2; P < .0001) 22 . Of the type C studies, no significant difference in OS was observed between patients with a high transfusion burden compared to patients who required ≤18 units of RBC over a period of 3 years of follow‐up ( P = .72185) 23 …”
Section: Resultsmentioning
confidence: 92%
“…After applying the inclusion/exclusion criteria, 75 studies were excluded for containing outcomes other than OS, and 16 studies excluded due to lack of required results. The final list included ten studies for qualitative analysis: six published articles 18‐23 and four abstracts 24‐27 (Figure 1). These ten studies were added to the list of studies included by Harnan et al (2016; 12 studies) 15,28‐39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In another study by Sotirova et al, patients with ferritin <500 µg/L were shown to have better OS. 19 Kikuchi et al found that serum ferritin levels of higher risk MDS patients were significantly higher than lower risk patients. Interestingly, ferritin levels of MDS patients with chromosomal abnormality were significantly higher than patients with normal karyotype.…”
Section: Figurementioning
confidence: 99%
“…2,3 Various prognostic indicators used in previous studies in myelodysplastic syndrome include clinical factors like age, gender, comorbidities and laboratory variables like haemoglobin levels, serum albumin, red cell distribution width, mean corpuscular volume, serum ferritin and lactate dehydrogenase. 4,5,6,7,8,9 Multiple studies from the west have shown serum albumin levels at presentation to correlate well with prognosis of patients. 4,10,11,12,13 Studies from India investigating the levels of serum albumin with prognosis of patients with myelodysplastic syndrome are scanty.…”
mentioning
confidence: 99%